2021
DOI: 10.3390/vaccines9020175
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Vaccine Hesitancy to a COVID-19 Vaccine in Cameroonian Adults and Its Global Implication

Abstract: Since the outbreak of COVID-19 in December 2019, no global consensus treatment has been developed and generally accepted for the disease. However, eradicating the disease will require a safe and efficacious vaccine. In order to prepare for the eventual development of a safe and efficacious COVID-19 vaccine and to enhance its uptake, it is imperative to assess vaccine hesitancy in Cameroonians. After obtaining ethical clearance from the Institutional Review Board of the University of Buea, a questionnaire was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
174
4
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(195 citation statements)
references
References 23 publications
9
174
4
8
Order By: Relevance
“…However, with the exception of the rural pastoralist site, income was not associated with vaccine hesitancy. Other studies reported less vaccine hesitancy among higher income groups [13,27]. These findings illustrate variations among certain sub-groups in the population and hence the need for focussed messaging and campaigns aimed at specific target groups that are more likely to be vaccine hesitant.…”
Section: Discussionmentioning
confidence: 53%
“…However, with the exception of the rural pastoralist site, income was not associated with vaccine hesitancy. Other studies reported less vaccine hesitancy among higher income groups [13,27]. These findings illustrate variations among certain sub-groups in the population and hence the need for focussed messaging and campaigns aimed at specific target groups that are more likely to be vaccine hesitant.…”
Section: Discussionmentioning
confidence: 53%
“…Also, these studies were conducted in countries with more advanced and organised public healthcare system. In Cameroon a study carried out by Dinga et al revealed a low acceptance (15.84%) of COVID-19 in the general population [22]. HCWs are regarded as role models and their non-acceptance of COVID-19 vaccines could indirectly in uence non-acceptance in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…another wondered if, "the vaccine sent to Africa will be of poor standards." 42 The Africa CDC study, stated that 31% or participants said that the type of vaccine would have an impact on uptake and 33% that the country of manufacture would have an impact on their willingness to be vaccinated. 4 As noted by Desclaux, "international solidarity for an equitable COVID-19 vaccine is also not very visible in Africa which may led to people rejecting the vaccine as part of a broader identity politics".…”
Section: Box 1 : Illustrative Quotes On Vaccine Accessmentioning
confidence: 99%